The identity of the Brachyplatys species recently introduced to Panama, with a review of bionomics (Hemiptera: Heteroptera: Plataspidae) - Rédei, Dávid (Zootaxa, 2016)
A recent report of a population of Brachyplatys vahlii (Fabricius, 1787) (Hemiptera: Heteroptera: Plataspidae) introduced to Panama is considered as misidentification, the species in concern is recognized as B. subaeneus (Westwood, 1837). Syntypes of B. subaeneus and diagnostic characters of the species are illustrated, published information on its distribution, bionomics and economic importance is reviewed. Syntypes of B. vahlii are illustrated, taxonomic problems in connection with the species are highlighted.